Experimental Analysis of Long Term Evolution Using Vector Signal Transceiver (VST) (International Journal of Engineering and Computer Science, 2017)
Long Term Evolution (LTE) has been introduced by 3rd Generation Partnership Project and dominates the 4th generation of mobile telecommunication network. LTE provides significantly increased peak data rates, with the potential for 100 Mbps downstream and 30 Mbps upstream, reduced latency, scalable bandwidth capacity, and backwards compatibility with existing GSM and UMTS technology. Future developments to could yield peak throughput on the order of 300 Mbps. In this article the performance of LTE system is experimentally evaluated based on VST 5644 using the modulation scheme like QPSK.